Evaluation of Serum Biochemical Parameters in Male Wistar Rats Administered with Azadirachta Indica Silver Nanoparticles - Arowora, Kayode Adebisi; Ugwuoke, Kenneth Chinekwu; Abah, Moses Adondua; Dauda, Abdulrashid; Ruyati, Samuel Sunny (Darul Yasin Al Sys, 2024)
The excessive exposure to silver nanoparticles (AgNPs) has raised concerns about their possible risks to the human health. This study investigated the effects of administering silver nanoparticles on serum biochemical parameters in male wistar rats. Synthesis of AgNPs from AgNO3 and plant extract was achieved using standard methods. At the same time, the characteristic peak of the synthesized AgNPs was determined using a UV-VIS spectrophotometer at a resolution of 1 nM. The crystal structure of AgNPs was determined using the Fourier Transform Infrared Spectroscopy (FTIR), while kidney and liver function parameters were carried out using serum with the aid of biochemical kits. A total of sixteen male wistar rats were randomly allotted into four experimental groups of four rats per group. Group 1 served as the control and received potable water. Groups two, three and four were orally administered with varying concentrations of silver nanoparticles (AgNPs) at 100, 250 and 500 mg/kg daily for two weeks respectively. Following cessation of treatments, rats were sacrificed under anaesthetization, and serum samples were collected for analysis. The result revealed that the absorption characteristic peak of the ultraviolet-visible spectrum of the silver nanoparticles synthesized was 450 nM. It was also observed that the urea, creatinine, and potassium ion (K+) had no significant difference (P>0.05). However, the values of total bilirubin (11.00±3.68 mg/dl) and Sodium ion (140.00±3.54) in group 4 decreased significantly (P<0.05) when compared to group 2, 3 and the control group. Also, it was observed that there is a significant increase (P<0.05) in the value of Chloride ion in all the administered group when compared to the control. Synthesized silver nanoparticles from A. indica also affected the level of liver parameters such as ALT, ALP, TP AST, and Albumin in a non-significant way. This study found no evidence of hazardous effects from silver nanoparticles, which could be attributed to the minimal dosage of AgNPs or the nanoparticles' source.